Serum value of IL-6 and TNF-α, Hct, arterial blood gas analysis after Application of improved ultrafiltration in extracorporeal circulation valve replacement surgery: Serum value of IL-6 and TNF-α, Hct, arterial blood gas analysis - Ning, Geng (Journal of Medical Biochemistry, 2025)
Objective: To investigate the effects of improved ultrafiltration in extracorporeal circulation valve replacement surgery. Methods: A total of 62 patients with valvular disease who underwent valve replacement were included and randomly divided into conventional ultrafiltration group (CUF group, n=31) and modified ultrafiltration group (MUF group, n=31). The Hct values, volume of pleural fluid drainage at 24 h after operation, ICU stay time, postoperative 24 h blood loss, bank blood usage, postoperative 24 h urine volume, ventilator support time, cardiac function indexes, postoperative changes of respiratory function and levels of inflammatory factors in both groups were compared. Results: After ultrafiltration, the Hct value in MUF group was significantly higher than CUF group, and the volume of pleural fluid drainage, blood loss, bank blood usage, urine volume and ventilator support time 24 h after operation were lower in MUF group (P<0.05). After surgery, LVEF levels were elevated, and those in MUF group were higher than CUF group. LVEDD and HR levels were declined in both groups after surgery, and were lower in the MUF group than CUF group (P<0.05). After ultrafiltration, the OI value in MUF group was higher and the P (A-a)O2 value was lower than CUF group (P<0.05). The plasma concentrations of IL-6 and TNF-α were increased after cardiopulmonary bypass (CPB) in both groups, and then declined after ultrafiltration, and IL-6 and TNF-α levels in MUF group were decreased compared to CUF group (P<0.05). Conclusion: MUF can control the ultrafiltrate time and levels, attenuate the postoperative systemic inflammatory response, reduce the lung injury caused by CPB, and improve the lung function of patients in the early postoperative period. It is of clinical significance in patient recovery after cardiac surgery, and shows the potential in heart valve replacement.